INFLUENCE OF SOCIAL MEDIA THROUGH INSTAGRAM (@tridaya. Cirebon) TO PURCHASE DECISION WITH BRAND AWARENESS AS VARIABLE INTERVENING - Handono, Artiar Anjani; Madiawati, Putu Nina (STIE Kusuma Negara, 2019)
Tridaya is one of the tutoring service providers in Indonesia, has a spread of 26 branches throughout Java. One of the branches is in Cirebon city. Along with the development of the current digitalization, it can also affect the environment of the increasingly dynamic, one of which is the use of social media as a platform that supports the development of social relations through cyberspace. Due to the many users, making business people feel that with the development of the number of social media users today, can also support their business to remain sustainable. So researchers want to know the impact of social media through Instagram to purchase decisions through brand awareness as a variable intervening is the purpose of this research. The method of data analysis used in this research is Structural Equation Modeling (SEM), which uses data processing application SmartPLS. In the results of a descriptive study of the respondents responses to the social media variables, variable brand awareness and variable purchase decisions are in good category. As for the hypothesis testing conducted by looking at the T-Statistic value of the results of the data show that all the proposed hypothesis was received, so it can be concluded that in this study the impact of social media through Instagram @tridaya. Cirebon has a positive and significant effect on purchasing decisions with variable brand awareness as a Intervening medium.